TEORI MUTASYÀBIH MAŠÀNÌ (Tawaran Teori Baru dalam Studi Al-Qur’an) - Abdurrahman S.HI.,M.Pd (lp2m-uin malang, 2013)
TEORI MUTASYÀBIH MAŠÀNÌ (Tawaran Teori Baru dalam Studi Al-Qur’an) Oleh: Abdurrahman, S.H.I., M.Pd. Dosen STAI Al-Qolam Gondanglegi Malang Email: abdurrahman@staialqolam.com Astract God proclaims the Quran as a holy book with a mutasyàbih and masani character. According to the common transliteration, referred to a book that uses repetition system (mašànì), with editorial and content similarity, so there is no contradiction in it (mutasyàbih).The two charactersbecomes a powerful system in all parts of the Qur'an,aspecially when correlated with the concept of